Use of biosolids for sod production: Impact on the import/export of nutrients, heavy metals, and soil mineral matter. (26th February 2020) - Griffith, Shane; Bero, Nicholas; Stier, John; Obear, Glen; Ruis, Sabrina J.; Soldat, Douglas
Abstract: Sod production has been criticized as being unsustainable because of the soil export that occurs at each harvest. Wastewater treatment residuals (biosolids) disposal is often limited by nutrient or metal accumulation in the soil. Biosolids‐based sod production may be a solution to minimize soil loss and land‐apply wastewater residuals. The objectives of this study were to assess biosolids‐based sod production impact on import and export of nutrients, heavy metals, carbon, and to quantify soil loss from sod harvest with and without biosolids. Anaerobically digested, dewatered sludge (Cake) and Cake mixed with sand and sawdust (MetroMix) were applied at three rates based on estimated plant available nitrogen (PAN). An additional treatment mimicked conventional sod production practices that rely on synthetic fertilizer. All biosolids rates and sources increased Mehlich‐3 extractable phosphorus (P) to > 175 mg kg −1 in the harvested sod, which could contribute to P runoff or leaching at the site of establishment. Heavy metal concentrations from both biosolids sources were below EPA loading limits and would require over 200 years of regular application (22 Mg ha −1 ) to exceed EPA maximum cumulative loading limits. Biosolids at 22 Mg ha −1 did little to reduce soil mineral matter loss compared to conventionally grown sod. After two sod production cycles, soil carbon increased by 50% in the surface soil (0–10 cm), but was reduced at a depth of 20–30 cm. While high P concentrations in the biosolids limit repeated applications, moderate use of biosolids may alleviate reliance on synthetic fertilizers for N and P.